STRENGTHENING LITERACY CAPACITY IN LEDOKTEMPURO VILLAGE: A COMMUNITY SERVICE COLLABORATION - Pratama, Bayu Indra; Sekti Ari, Dessanti Putri; Swastikawara, Sinta; Wahid, Abdul (Erudio Journal of Educational Innovation, 2025)
This activity results from a collaboration between the lecturers' community service program and the Kuliah Kerja Nyata (KKN)/Student Community Service for Mahasiswa Membangun Desa (MMD) at Universitas Brawijaya. It will take place in July 2025 in Ledoktempuro Village, Randuagung District, Lumajang Regency. The initiative was driven by concerns about the low interest in reading among the village community. This collaboration uses an Action Research approach, with lecturers as project leaders, students as facilitators for mentoring activities, and the community as participants. The stages include identifying problems, developing action plans, implementing activities, and reflecting on outcomes to assess the program’s impact on citizen participation. The team identified two main issues: low reading interest within families and a lack of village reading facilities. The community service aims to spark reading activities and establish suitable reading facilities for residents. Results show that children gained confidence and expressed themselves through reading aloud (Membaca Nyaring), revitalizing the library and leading to the development of adequate reading facilities. Additionally, residents' interest in visiting the village library increased, highlighting the need for ongoing activities to maintain community engagement. Building volunteers’ capacity in the future is essential for sustaining the village library's activities and management.